IMPLIKASI STRATEGI GURU PENDIDIKAN AGAMA HINDU DAN BUDI PEKERTI TERHADAP PENGUATAN INDIKATOR MODERASI BERAGAMA DI SD SARASWATI 6 DENPASAR - I Dewa Gede Darma Permana (Jurnal Pendidikan Agama, 2023)
Ethnocentrism, exclusivity, and intolerance are challenges that a pluralistic country like Indonesia must face. Considering these problems, a strategy by teachers is needed to strengthen the existence of religious moderation in the school environment, such as what is done by Hindu Religious Education and Ethics teachers at Saraswati 6 Denpasar Elementary School (SD Saraswati 6 Denpasar). Reflecting on this, this study is interested in presenting the implications of the Hindu Religious Education and Ethics teacher's strategy for strengthening indicators of religious moderation. The formulation of the problem in this study is answered systematically, starting from the implications of strengthening indicators of national commitment, tolerance, non-violence, and accommodation of local culture. The research method in this paper is a qualitative type of research with a descriptive naturalistic-based field research approach. The data sources used come from primary and secondary sources. Data collection methods that use observation techniques, interviews, literature studies, and data analysis that uses the approach of Miles and Huberman. The results of this study indicate that the strategies implemented by Hindu Religious Education and Ethics teachers are able to have a positive impact on strengthening indicators of religious moderation at SD Saraswati 6 Denpasar, both in terms of indicators of national commitment, tolerance, non-violence, and accommodation of local culture. The results of this paper are intended as guidelines for teachers to anchor the concept of religious moderation in schools.